Multi-level education for sustainability through global citizenship, territorial education and art forms - Simon, Sandrine; Vieira, Inês; Jecu, Marta (Frontiers in Education, 2023)
This article is aimed at addressing concepts, approaches and challenges that are both very characteristic of the era we are living in and that would also greatly benefit from being more and better integrated into our learning systems (both in the formal and non-formal educational systems and lifelong learning). Those issues and themes have emerged from, or have been exacerbated by, socio-economic systems in place since the middle of the 20th century, promoting amongst other things, a consumption society based on a linear over-exploitation of natural resources, the globalization of exchanges, a rapid urbanization process and not-always-harmonious mixes of cultures and communities. The Covid-19 pandemic seems to have culminated in triggering reflections on what matters most and, conversely, on what makes our world so un-sustainable and non-resilient. From these, a new momentum has been generated on reviewing where our efforts on teaching and learning about ‘sustainability’ got us to. Our focus here is on new approaches to education for sustainability at global, community and personal levels, as well as at levels that connect those. From linking the local to the global through ‘global citizenship’, to experiential learning generated through practical projects such as urban agriculture, to an emotional involvement into understanding sustainability issues through art forms, we re-visit sustainability through the eyes of the learners, questioning the boundaries of the ‘sustainability educational project’ beyond the ones which, for (too) long, have paralleled those of neo-liberal reforms.